TASK-BASED LANGUAGE TEACHING: ADVANTAGES AND CHALLENGES IN EFL CLASSROOMS. - Bozorboeva Lobar Alisher qizi (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract:  Task-Based  Language  Teaching  (TBLT)  has  garnered  widespread attention in the context of English as a Foreign Language (EFL) instruction because of its learner-centered orientation and communicative authenticity. This article explores both the advantages and the challenges of implementing TBLT in EFL classrooms, drawing  on  empirical  studies  and  theoretical  discussions.  It  examines  how  TBLT fosters communicative competence, learner motivation, and contextualized language use,  while  also  considering  constraints  such  as  teacher  preparedness,  assessment alignment, classroom management, and cultural expectations. Implications for practice and future research directions are presented.